2005
DOI: 10.2174/1568009054629663
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Efficacy of Angiotensin II Receptor Blockers in Prostate Cancer

Abstract: An apparent low prevalence of cancer in hypertensive patients receiving angiotensin converting enzyme inhibitors is reported; however, the molecular mechanisms have not been elucidated. Angiotensin-II (Ang-II) is well known to be associated with hypertension, as a main peptide of the renin-angiotensin system, and its detailed molecular mechanisms have recently been elucidated. For instance, Ang-II directly activates the mitogenic signal transduction pathway through the angiotensin-II type-1 (AT1) receptor in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 134 publications
(169 reference statements)
2
30
0
Order By: Relevance
“…More surprisingly, there is considerable evidence that the male reproductive organs contain reninangiotensin system components, such as angiotensinogen, renin, angiotensin I -converting enzyme, and AT 1 and AT 2 receptors. O'Mahony et al suggested that the prostate gland may be the source of angiotensin II found in seminal fluid and that angiotensin II production may be regulated by androgen (39,40). Based on this accumulated evidence and our results, the prostate itself seems to be a target for angiotensin, and the prostatic renin-angiotensin system may affect the development of prostate cancer.…”
Section: Discussionsupporting
confidence: 72%
“…More surprisingly, there is considerable evidence that the male reproductive organs contain reninangiotensin system components, such as angiotensinogen, renin, angiotensin I -converting enzyme, and AT 1 and AT 2 receptors. O'Mahony et al suggested that the prostate gland may be the source of angiotensin II found in seminal fluid and that angiotensin II production may be regulated by androgen (39,40). Based on this accumulated evidence and our results, the prostate itself seems to be a target for angiotensin, and the prostatic renin-angiotensin system may affect the development of prostate cancer.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, we have reported that angiotensin II affects the signal pathways in prostate cancer cells. Angiotensin II activates the signal transduction of mitogen-activated protein kinase and signal transducers and activators of transcription 3 and angiogenesis in prostate cancer cells (15). Also, angiotensin II facilitates the secretion of some growth factors and cytokines from prostate stromal cells, resulting in cell proliferation of prostate cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their intraglomerular hemodynamic effects, these drugs might diminish proteinuria and ameliorate diabetic nephropathy by other mechanisms. One interesting possibility, currently described in tumor angiogenesis, is that ACEI and ARB have antiangiogenic effects by reducing endothelial cell migration, tube formation, and Ang II-dependent productions of VEGF (11)(12)(13).…”
mentioning
confidence: 99%